2012
DOI: 10.1111/j.1468-2958.2011.01425.x
|View full text |Cite
|
Sign up to set email alerts
|

Think-Aloud Process Superior to Thought-Listing in Increasing Children's Critical Processing of Advertising

Abstract: This study develops and tests a model of children's critical processing of advertising. Within this model, 2 paths to reduced advertising susceptibility (i.e., attitude toward the advertised brand) were hypothesized: a cognitive path and an affective path. The secondary aim was to compare these paths for different thought verbalization processes: think‐aloud and thought‐listing. The model was tested on a sample of 8‐ to 12‐year‐old children (N = 163). Structural equation modeling revealed that, for children in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 57 publications
2
41
0
1
Order By: Relevance
“…de Droog, S. M., Buijzen, M., & Valkenburg, P. (2012 To explore the relative endorsement effect: which of the two endorsers is more effective? Does NOT show net endorsement effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…de Droog, S. M., Buijzen, M., & Valkenburg, P. (2012 To explore the relative endorsement effect: which of the two endorsers is more effective? Does NOT show net endorsement effect.…”
Section: Resultsmentioning
confidence: 99%
“…Between 8 -12 years old, children largely possess conceptual advertising literacy but cannot spontaneously retrieve and apply it while processing the commercial (John, 1999; Brucks, Armstrong & Goldberg, 1989;Rozendaal, Buijzen & Valkenburg, 2012; Dixon et al, 2013). Children above twelve years old, on the other hand, are expected to be able to employ their advertising literacy as a defense (Buijzen, Van Reijmersdal, & Owen, 2010).…”
Section: Systematic Review Of Child-targeted Food Endorsementmentioning
confidence: 99%
“…Those few systematic studies which are available (Brucks, Armstrong & Goldberg, 1988;Rozendaal, Buijzen & Valkenburg, 2012) suggest that younger children (from 7 to 12) only activate and apply their knowledge when watching advertisements, if they have previously been given a trigger to do so, for example by an educational film on the nature of advertising. Moreover, Rozendaal et al (2012) showed that strategies which explicitly make students more aware of their own critical thoughts about advertising (such as think-aloud activities) clearly reduce advertising susceptibility. Overall, advertising research suggests that activities which intensively deal with advertising and thereby increasing student awareness of the corresponding knowledge can effectively lead to a more critical view of advertising.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…This can be explained by the fact that children do not fully understand the persuasive character of these formats while they love them, leading to less irritation and resistance towards such advertisements. In other words, children appear to have lower levels of cognitive and affective advertising literacy for such new formats (defined as the skills of analyzing and evaluating persuasive messages across a variety of contexts and media; Rozendaal et al, 2012). This limited advertising literacy may lead to a higher impact of these formats, both in terms of intended (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this interactive nature, children are strongly involved with the game, resulting in a higher focus and the feeling of immersion in the online game (Cauberghe and De Pelsmacker, 2010;Escalas, 2004;Hsu and Lu, 2004). Although both AFPs and advergames might be very liked by children, the absortion and potential state of flow caused by the interactivity may affect children's affective advertising literacy level, that is described as their critical attitude towards the advertising format (Boerman et al, 2012;Rozendaal et al, 2012), more strongly and in a negative way (Escalas, 2004) (Privette, 1983). When playing an advergame, children's critical processing of an embedded ad is less likely, than when passively watching an AFP.…”
Section: Children's Advertising Literacy Level For Advergames Versus mentioning
confidence: 99%